Unsafe Work Environment At Construction Workplace: A Legal Implications - Rahim, Rohani Abdul; Mohd Zin, Sufri; Landa, Azizah (Universiti Sains Malaysia, 2016)

(untitled)
The recent 11th Malaysian Plan (2016-2020), showed that the Government will continue to map out its approach to upgrade physical infrastructure in the next five years. It will become the multiplier effect that continue to be the catalyst to the other sectors to attract domestic and foreign investments to support the country’s economic growth. Construction growth (GDP) to remain robust with the Government’s GDP forecast of 10.7% for the sector in 2015. This scenario claim relevancy to place great concern on the occupational health and safety in construction work. This need be reflected in the many preventive measures taken to minimize the hazard and the risks that the workers are exposed. Literature claims that accidents occur due to three main causes that are (a) failure to continuously in stages, to identify unsafe work conditions and environment, (b) unscrupulous decision to continue work knowingly even when unsafe conditions identified by workers, and (c) to act unsafely and jeopardizing workers safety and life as well as the workplace. This paper will examine the nature of unsafe work environment at construction workplace, the risk and hazards identified and the relevant laws and procedures available in Malaysia to ensure work safety practice in the construction work sites. Finally, to identify some of the preventive and innovative measures needed to ensure safety work environment at work sites. This exposure will helps to explain better on the accidents on construction sites and in identifying areas where prevention efforts should be directed, so that labour and management may provide more effective measures for preventing accident occurrence.